Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1074/jbc.m116.740563
|View full text |Cite
|
Sign up to set email alerts
|

ATP hydrolysis Promotes Duplex DNA Release by the RecA Presynaptic Complex

Abstract: Homologous recombination is an important DNA repair pathway that plays key roles in maintaining genome stability. Escherichia coli RecA is an ATP-dependent DNA-binding protein that catalyzes the DNA strand exchange reactions in homologous recombination. RecA assembles into long helical filaments on single-stranded DNA, and these presynaptic complexes are responsible for locating and pairing with a homologous duplex DNA. Recent single molecule studies have provided new insights into RecA behavior, but the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…Recent single-molecule data also demonstrated the additional function of RecA ATPase activity in homology searching is to stimulate the bypass of heterologous contact by increasing dsDNA turnover,s trand exchange kinetics under ATPi sa ccordingly faster than that in ATPgS. [32] Consistent with these notions, our data showedareductioni ns trand exchange efficiency when ATPh ydrolysis is abolished ( Figure 1B). Previous work using either the 229/149 hybrid DNA or the 427/352h ybrid DNA returnsw ith similar strand exchange efficiencies.…”
Section: Dna Topology Strongly Affects the Strand-exchange Efficiencysupporting
confidence: 87%
See 1 more Smart Citation
“…Recent single-molecule data also demonstrated the additional function of RecA ATPase activity in homology searching is to stimulate the bypass of heterologous contact by increasing dsDNA turnover,s trand exchange kinetics under ATPi sa ccordingly faster than that in ATPgS. [32] Consistent with these notions, our data showedareductioni ns trand exchange efficiency when ATPh ydrolysis is abolished ( Figure 1B). Previous work using either the 229/149 hybrid DNA or the 427/352h ybrid DNA returnsw ith similar strand exchange efficiencies.…”
Section: Dna Topology Strongly Affects the Strand-exchange Efficiencysupporting
confidence: 87%
“…In the absence of ATP hydrolysis, RecA could not dissociate from DNA and likely can't release torsional strain accumulated in DNA. Recent single‐molecule data also demonstrated the additional function of RecA ATPase activity in homology searching is to stimulate the bypass of heterologous contact by increasing dsDNA turnover, strand exchange kinetics under ATP is accordingly faster than that in ATPγS . Consistent with these notions, our data showed a reduction in strand exchange efficiency when ATP hydrolysis is abolished (Figure B).…”
Section: Dna Topology Strongly Affects the Strand‐exchange Efficiencysupporting
confidence: 87%
“…In these studies, D-loop intermediates were generated by incubating RecA, RAD51 or DMC1 presynaptic complexes with fluorescently tagged dsDNA fragments containing an internal microhomology of 8–15 nucleotides in length, which was complementary to the ssDNA. The resulting lifetime changes occurred in 3-nucleotide increments, consistent with the notion that strand exchange intermediates are stabilized by the RAD51/RecA family members in 3-nucleotide steps 9294 . Moreover, the energetic signature of the stepping behaviour was conserved for RecA, RAD51 and DMC1, indicating that this behaviour appears to be broadly conserved among members of the RAD51/RecA family of DNA recombinases.…”
Section: Sm-based Insights Into Recombinationsupporting
confidence: 80%
“…Subsequent analysis of the delay time distributions suggested that strand exchange took place in 3-nucleotide steps 112 . Similar stepping behaviours during strand invasion have been observed using ssDNA curtain assays 9294 . In these studies, D-loop intermediates were generated by incubating RecA, RAD51 or DMC1 presynaptic complexes with fluorescently tagged dsDNA fragments containing an internal microhomology of 8–15 nucleotides in length, which was complementary to the ssDNA.…”
Section: Sm-based Insights Into Recombinationsupporting
confidence: 76%
See 1 more Smart Citation